MODIFIKASI ALAT PENYANGRAI KOPI MEKANIS TIPE ROTARI (Modification of Mechanical Coffee Roasters Equipment Rotary Type) - Khoirul Ajmi Siregar; Achwil Putra Munir; Sulastri Panggabean (Universitas Sumatera Utara, 2017)
ABSTRACT Roasting isan important stepin the production ofcoffee powder, where inthe formation ofaromaanddistinctiveflavourof coffeeis enhancedat this stage. From nationalproductionof coffee beans,only 20% areprocessed andmarketedin the form ofsecondaryproductssuch as roastedcoffee, ground coffeeand instant coffee. This studywas plan to modifymechanicalcoffeeroastersequipment rotarytype. The study was conductedwith literature study, experiment, observationand testingof theequipment. Parameters observed were the effective capacity ofthe equipmentand economic analysis.Based on this research, it was summarized that the effective capacity of the equipment was 2.96kg/hour. The economic analysis was as follows: basic costs for the first to the fifth year wereRp. 6703,04/kg, Rp. 6713,34/kg, Rp. 6724,63/kg, Rp. 6736,76/kgandRp. 6749,81/kg respectively. The break even pointwas 264,54 kg/year. The net present value was Rp. 125.277.927. The internalrate of returnwas 50%. Keywords:postharvestequipment, coffee, roasting, effectivecapacity ABSTRAK Proses penyangraian adalah tahapan penting dalam produksi kopi bubuk, dimana pembentukan aroma dan cita rasa khas kopi ditentukan pada tahapan ini. Dari produksi biji kopi nasional hanya 20% yang diolah dan dipasarkan dalam bentuk produk kopi skunder seperti kopi sangrai, kopi bubuk dan kopi cepat saji. Penelitian ini adalah sebuah modifikasi alat penyangrai kopi mekanis tipe rotari. Penelitian dilakukan dengan teknik studi literatur, melakukan eksperimen, pengamatan dan pengujian terhadap alat. Parameter yang diamati yaitu kapasitas efektif alat, dan analisis ekonomi. Dari hasil penelitian diperoleh kapasitas efektif alat sebesar 2.96 kg/jam. Analisis ekonomi, biaya pokok untuk tahun pertama sampai tahun kelima berturut-turut yaitu Rp. 6703,04/kg, Rp. 6713,34/kg, Rp. 6724,63/kg, Rp. 6736,76/kg dan Rp. 6749,81/kg. Break even point yaitu sebesar 264,54 kg/tahun. Net present value sebesar Rp. 125.277.927. Internal rate of return adalah sebesar 50%. Kata kunci:alat pasca panen, kopi, penyangraian, kapasitas efektif.